Komunitas Gulma pada Sistem Tumpangsari Jagung Manis dengan Lima Jenis Kacang - Octavia, Sri Devi; Setiyawan, Andre (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Sweet corn (Zea mays saccharata Sturt) is usually grown in monoculture with wide spacing, which stimulates the growth of weeds around the maize. Weed management is mostly carried by chemicals, which could have a negative environmental impact. One technique to reduce this negative impact is the intercropping system. This study aimed to determine the diversity of weeds and the effectiveness of legumes in suppressing weed growth in intercropping systems. The experiment was designed as a single factor randomized complete block design (RCBD) with three replications. The treatment consisted of five types of legumes: groundnut, soybean, kidney bean, cowpea, and mungbean. The control consisted of a monoculture of sweet corn and legumes. The results showed that 33 types of weeds were present in the intercropping system, with the dominant species being Cyperus rotundus, Cynodon dactylon, Physalis angulata, and Phyllanthus niruri. Intercropping with all species of legumes and sweet corn can suppress weed growth without reducing sweet corn yield. Intercropping sweet corn and cowpea had the highest ability to suppress weeds